Forage Report 2016 - J. D. Holman; G. Cramer; A. Esser; Jane Lingenfelser; S. Maxwell; J. L. Moyer; A. Obour; T. Roberts (Kansas Agricultural Experiment Station Research Reports, 2017)
In 2016 summer annual forage variety trials were conducted across Kansas near Garden City, Hays, Hutchinson, Mound Valley, and Scandia. All sites evaluated hay and silage entries. Companies were able to enter varieties into any possible combinations of research sites, so not all sites had all varieties. Across the sites, a total of 99 hay varieties and 99 silage varieties were evaluated.
Keywords: Forage